Hubungan Kejadian Fibrilasi Atrium dengan Diameter Atrium Kiri pada Fibrilasi Atrium Valvular dan Fibrilasi Atrium Non-Valvular Di RSUD Arifin Achmad - Sri Adeyana; Haryadi Haryadi; Chandra Wijaya (Fakultas Kedokteran Universitas Riau, 2017)
Atrial Fibrillationis a kind of arrhythmia which has the most incidence. Based on its Etiology, atrial fibrillationcouldbe divided in to two, valvular and nonvalvular atrial fibrillation. This study was aimed toknow the correlation ofatrial fibrillation incidence between valvular and nonvalvular with its left atrium diameter in Arifin Achmad ProvinsiRiau’s General Hospital. This study was analytical and done by cross sectional approach with 185 patient. The datawere processing with computerize to univariate analysis and chi-square for bivarite analysis. From this study it can beconcluded that the most occurrence of atrial fibrillation was non valvular atrial fibrillation which was 76,8% with theetiology mostly of hypertension which was 41,5%. Valvular atrial fibrillation was mostly caused by mitral stenosiswhich was 37,2% and there were no correlation between the diameter of left atrium to the occurrence of valvular andnon valvular atrial fibrillation (p=0,273.)